The refugee crisis, non-citizens, border politics and education. Issue 6 (2nd November 2017) - Gerrard, Jessica
ABSTRACT: In the midst of the most serious refugee crisis since WWII, nation states are buttressing their borders. This paper explores the border politics of the nation state in response to the refugee crisis. Drawing on the work of Susan Sontag, Judith Butler and Imogen Tyler it considers the ways in which the imagery of the pain and suffering of Others is deployed to bolster concerns surrounding the sovereignty and safety of the nation state. I suggest the proliferation of 'non-citizen spaces', such as refugee detention camps, indicate the need to re-examine the border practices of the nation state amidst contemporary globalisation, and re-consider the limits of popular – and often taken for granted – notions of 'global citizenship' in education research and practice. This involves, I contend, understanding concepts and practices of migration, transition and the global as mediated in and through the fortification of nation state borders.